Ethnosocial consequences of the resettlement policy of the USSR in the Urals in the late 1920s - Kamenskikh, M.S. (Perm Federal Research Centre Journal, 2018)
In the article, based on unpublished archival materials and and field research, census data materials, the analysis of the progress and success of the resettlement campaign in the Urals in the 1928-1930s are described. The author considers the results of the migration campaign of Chuvash and Ukrainians in the Urals region in terms of their influence on the ethnic structure of the population and the formation of ethno-disperse groups in the region.